Individual Observer Differences in the Use of Form and Motion to Perceive the Actor's Sex in Biological Motion Displays. Issue 1 (February 2022) - Hiris, Eric; Conway, Sean; McLoughlin, William; Yang, Gaokhia
Recent research has shown that the perception of biological motion may be influenced by aspects of the observer's personality. In this study, we sought to determine how participant characteristics (including demographics, response inhibition, autism spectrum quotient, empathy, social anxiety, and motion imagery) might influence the use of form and motion to identify the actor's sex in biological motion displays. We varied the degree of form and motion in biological motion displays and correlated 76 young adult participants' performances for identifying the actor's sex in these varied conditions with their individual differences on variables of interest. Differences in the separate use of form and motion cues were predictive of participant performance generally, with use of form most predictive of performance. Female participants relied primarily on form information, while male participants relied primarily on motion information. Participants less able to visualize movement tended to be better at using form information in the biological motion task. Overall, our findings suggest that similar group level performances across participants in identifying the sex of the actor in a biological motion task may result from quite different individual processing.